Public Service in Interpersonal Communication - Lusiawati, Ira (International Journal for Educational and Vocational Studies, 2019)
One important aspect in the implementation of public services is the ability of a service officer to interact and communicate with others. Communication is the most common thing in providing services. Good value whether or not a service is often seen from how the service providers in communicating with customers. For this communication skills must be owned and mastered properly by each service provider. In the implementation of public services, communication skills become one of the important aspects that will affect how effective the public services are provided and will determine how the community as a customer in responding to and imaging the funding organization. To communicate must be able to place humans in an honored position as well as public service is an effort to humanize humans (human humanization). In communication there is delivery of information and from one person to another. Communication will be good if there is mutual understanding between the sender and receiver of information so that the message conveyed is easily understood . This paper reviews the effectiveness of interpersonal communication within organizations to improve the quality of public services.